(3cJGH GdJfhjQs - (3GdMSf Hf fhM GdbeQj GdMcje, CHh efUhQ,J (B380 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd CHh efUhQ GdMSf Hf fhM GdbeQi Efi dcKQI eYQaJi HaVd Yde GdWH Ydi SGFQ GdYdhe hbO CMHHJ gPG GdhbJ Cf CdJbW ef HWhf GdcJH hJUGfja GdcJGHGJ CdaGXkG gi YfO Cgd GdUfGYI eYQhaI s
(3BNQgG (B:s
( (3GdejcQhajde ZjQ hGVM ai GdJUhjQ (B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B299s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eYgO GdESJTQGb (B- (3HWQSHQZ (B( (3QhSjG(B) (4686/386) s
Keywords: (3GdWHs